Congenital methemoglobinemia masquerading as spastic diplegic cerebral palsy - Sinha, Rahul; Singh, Sonali; Kamila, Gautam; Meena, Ankit (International Journal of Contemporary Pediatrics, 2022)
Congenital methemoglobinemia is an autosomal recessive condition resulting from deficiency of methemoglobin reductase which is caused by homozygous or compound heterozygous mutation in the CYB5R3 gene on chromosome 22q13, manifesting clinically by decreased oxygen carrying capacity of the blood, with resultant cyanosis and hypoxia. The clinical features include microcephaly, developmental delay, spasticity and myelination defects, seizures, feeding difficulties. Methemoglobinemia is an abnormal increase of MetHb (>3%) of total haemoglobin which can be either hereditary and acquired. The acquired methemoglobinemia is mostly due to anaesthetic drugs and genetic one is due to deficiency of CYB5R3 or cytochrome B5 systems. The type I congenital methemoglobinemia is more common and less severe and is caused by CYB5R functional deficiency in red blood cells compared to type II which is more severe and less frequent and CYB5R deficiency is present in all cells. Sometimes it might mimic as static insult sequalae in the form of spastic diplegia. Here we reported an 8-month-old female with spastic diplegia with recurrent episodes of bluish discoloration later found to have autosomal recessive congenital methemoglobinemia.